Sebaran Tanah Objek Reforma Agraria (Tora) di Kabupaten Sijunjung tahun 2021 dan Analisis Kelayakannya untuk Diredistribusikan kepada Masyarakat - Kabarulloh, Ahmad (DEPARTEMEN GEOGRAFI FIS UNP, 2025)
Agrarian Reform is an effort to reorganize the relationship between society and land, namely reorganizing the control, ownership, use and fair use of the earth's surface. Changes need to be made because until now there are still inequalities in the structure of control, ownership, use and utilization of land which results in income inequality and conflicts or land disputes. One form of implementation of Agrarian Reform activities in order to realize justice in terms of land is the implementation of the redistribution of Agrarian Reform Object Land but before the land is redistributed to the community, it is necessary to analyze the feasibility of the land for use by the community. This research is a descriptive research with a quantitative approach. The results showed that the location of TORA in Sijunjung Regency in 2021 has an area with a feasibility level of Redistribution of 1,176.9 Ha, an area with a Conditional Eligible eligibility level for redistribution of 22.2 Ha, and an area that is not Eligible for redistribution due to a limiting factor of 145.3 Ha. Keywords: TORA, eligibility level, TORA priority.